Death of a new American - Fredericks, Mariah (Fredericks, Mariah. Jane Prescott, 2019)
The atmospheric, compelling follow-up to the stunning debut A Death of No Importance, featuring series character, Jane Prescott. In 1912, as New York reels from the news of the Titanic disaster, ladies' maid Jane Prescott travels to Long Island with the Benchley family. Their daughter Louise is to marry William Tyler, at their uncle and aunt's mansion; the Tylers are a glamorous, storied couple, their past filled with travel and adventure. Now, Charles Tyler is known for putting down New York's notorious Italian mafia, the Black Hand, and his wife Alva has settled into domestic life. As the city visitors adjust to the rhythms of the household, and plan Louise's upcoming wedding, Jane quickly befriends the Tyler children's nanny, Sofia--a young Italian-American woman. However, one unusually sultry spring night, Jane is woken by a scream from the nursery--and rushes in to find Sofia murdered, and the carefully locked window flung open. The Tylers believe that this is an attempted kidnapping of their baby gone wrong; a warning from the criminal underworld to Charles Tyler. But Jane is asked to help with the investigation by her friend, journalist Michael Behan, who knows that she is uniquely placed to see what other tensions may simmer just below the surface in this wealthy, secretive household. Was Sofia's murder fall-out from the social tensions rife in New York, or could it be a much more personal crime?